Dementia Prevalence, Comorbidities, and Lifestyle Among Jatinangor Elders - Ong, Paulus Anam; Annisafitrie, Febby Rosa; Purnamasari, Novita; Calista, Chandra; Sagita, Noveline; Sofiatin, Yulia; Dikot, Yustiani (Frontiers in Neurology, 2021)
Introduction: Research on dementia prevalence and the potentially related risk factors from Indonesia is scarce. We sought to identify the prevalence of dementia, health risk factors, and lifestyle in Jatinangor elders. Methods: A total of 686 participants completed questionnaires on lifestyle, health risk factors, and cognitive and functional tests from September 2013 to December 2013. We determined the prevalence of dementia; and the associations between health, leisure activities, dietary pattern, and dementia were analyzed using logistic regression. Results: The prevalence of dementia was 29.15%. The risk factors differed between age groups. Those aged 60–74 years and who have a lower education level, lower occupational attainment, and less active intellectual and recreational activities were associated with higher dementia risk. Those aged > 75 years living in a rural area and who take less fruit were associated with a higher risk of dementia. Conclusions: The prevalence of dementia in Jatinangor is high. The identified modifiable risk factors are a potential target for intervention and valuable for designing public health policies.